Selective mRNA sequestration by OLIGOURIDYLATE-BINDING PROTEIN 1 contributes to translational control during hypoxia in Arabidopsis - Sorenson, Reed (National Academy of Sciences, 2014)
Low oxygen stress dynamically regulates the translation of cellular mRNAs as a means of energy conservation in seedlings of Arabidopsis thaliana. Most of the highly hypoxia-induced mRNAs are recruited to polysomes and actively translated, whereas other cellular mRNAs become translationally inactive and are either targeted for stabilization or degradation. Here we identify the involvement of OLIGOURIDYLATE BINDING PROTEIN 1 (UBP1), a triple RNA Recognition Motif protein, in dynamic and reversible aggregation of translationally repressed mRNAs during hypoxia. Mutation or down-regulation of UBP1C interferes with seedling establishment and reduces survival of low oxygen stress. By use of messenger ribonucleoprotein (mRNP) immunopurification, we show that UBP1C constitutively binds a subpopulation of mRNAs characterized by uracil-rich 3′-untranslated regions under normoxic conditions. During hypoxia, UBP1C association with non–uracil-rich mRNAs is enhanced concomitant with its aggregation into microscopically visible cytoplasmic foci, referred to as UBP1 stress granules (SGs). This UBP1C–mRNA association occurs as global levels of protein synthesis decline. Upon reoxygenation, rapid UBP1 SG disaggregation coincides with the return of the stabilized mRNAs to polysomes. The mRNAs that are highly induced and translated during hypoxia largely circumvent UBP1C sequestration. Thus, UBP1 is established as a component of dynamically assembled cytoplasmic mRNPs that sequester mRNAs that are poorly translated during a transient low energy stress.